Field report PAC 671: lack in auditing skills / Nur Syafizah Kamarudin - Kamarudin, Nur Syafizah (Universiti Teknologi MARA, Terengganu, 2024)
Aljeffridean PLT was a trusted business consultant. In addition to attending to the urgent needs and unique issues of clients, audit team can offer advice and support when it comes to financial decisions that will improve operations and boost company performance. The industries in which clients operate are diverse and include huge conglomerates, solo proprietorships, public and private corporations, government agencies, commercial institutions, co-ops, and non-profit organisations.